Toxoplasma chitinase-like protein orchestrates cyst wall glycosylation to facilitate effector export and cyst turnover - Yong Fu; Tadakimi Tomita; Louis M. Weiss; Christopher M. West; L. David Sibley (Proceedings of the National Academy of Sciences, 2025)
Toxoplasma bradyzoites reside in tissue cysts that undergo cycles of expansion, rupture, and release to foster chronic infection. The glycosylated cyst wall acts as a protective barrier, although the processes responsible for formation, remodeling, and turnover are not understood. Herein, we identify a noncanonical chitinase-like enzyme TgCLP1 that localizes to micronemes and is targeted to the cyst wall after secretion. Genetic deletion of TgCLP1 resulted in a thickened cyst wall that decreased cyst turnover, blocked the export of virulence effectors into host cells, and resulted in failure to persist during chronic infection. Genetic complementation with a series of mutants revealed that the GH19 glycosidase domain was crucial for regulating glycosylation of several glycoproteins in the cyst wall. Overall, our findings reveal that TgCLP1 is a multifunctional survival factor that modifies glycoproteins within the cyst wall to modulate export of virulence effectors and regulate turnover of tissue cysts.